The Impact of Cycle Threshold Value in Influencing the Performance of COVID-19 Antigen - Rivaldi Febrian; July Kumalawati; Nina Dwi Putri; Linny Luciana; Aria Kekalih (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
COVID-19 antigen is an alternative test for detecting SARS-CoV-2 infection. Viral load represented by the Cycle Threshold (CT) in the Real-Time Reverse Transcriptase Polymerase Chain Reaction (rRT-PCR) affects the diagnostic performance of the test. Higher CT values result in reduced sensitivity of the SARS-CoV-2 antigen. The main objective of this study was to determine the highest CT value in rRT-PCR that still yielded reactive results in the COVID-19 antigen test. This cross-sectional study was conducted at the Fever Outpatient Clinic in Dr. Cipto Mangunkusumo Hospital from July 2020 to June 2021. Two hundred and thirty-five naso-oropharyngeal swabs were taken from patients with confirmed and suspected COVID-19 diagnoses. About 24.7% of subjects were tested positive. The median highest CT value giving reactive COVID-19 antigen results was 28.22 (13.33-39.16), while the median CT value for non-reactive antigen results was 34.45 (26.08-39.65). At a CT value < 40, the COVID-19 antigen test demonstrated 63.8% sensitivity, 99.4% specificity, 89.3% Negative Predictive Value (NPV), and 97.4% Positive Predictive Value (PPV). At the CT value < 25, the test showed 92.3% sensitivity, 99.4% specificity, 99.4% NPV, 92.3% PPV, 163.4 LR+, and 0.1 LR-. The identified cut-off point for the CT value was 29.82, with a sensitivity of 64.9% and specificity of 81%. In conclusion, COVID-19 antigen is a valuable test for screening patients with symptoms of SARS-CoV-2 infection. Understanding the influence of cycle threshold can enhance the interpretation and reliability of the antigen test.